Determinación del rendimiento del cacao (Theobroma cacao l) clon bola, fecundado mediante hibridación y autopolinización, en el recinto Mata de Cacao - Fabián Enrique, Lema Cuji (2024)
In recent years, a decrease in production has been observed due to the size of the pod, thickness of the ridge and number of empty seeds, which directly influences the amount of cocoa produced per hectare, causing a loss of 5 to 10%. depending on the level of incompatibility of the genetic material in the town of Mata de Cacao. In the research carried out, the yield of cocoa (Theobroma cacao L) Clone Bola, fertilized through hybridization and self-pollination, in the Mata de Cacao enclosure was determined. The objectives set were: I) Identify the phenotypic differences between the fruits obtained by hybridization and self-pollination. II) Determine the yield of Clone Bola cocoa fertilized under hybridization and self-pollination. The treatments under study were: T1 Bola Clone + CCN51, T2 Bola Clone + INIAP - EETP – 800, T3 Bola Clone + JHVH 10, T4 Bola Clone + FA-2003 and T5 Self-pollinations. Descriptive statistics were used. The type of analysis, Fisher's test at 5%, Tuckey's test at 5% and correlation and linear regression analysis. The variables were evaluated: Ear length (LM), Ear diameter (DM), Seed width (AS), Seed length (LS), Number of empty seeds (NSV), Number of harvested ears (NMC), Incidence of monilla on cob (IMM), Grains per cob (GM), Ridge thickness (EC), Furrow depth (PS), Weight of wet seed with pulp and testa (PSH), Seed index (IS), Ear index (IM), Dry seed weight (PS) and Yield (Kg/ha). According to the results obtained, they indicate that T1, T3 and T4 hybrids have a lower incidence of wasted seeds, which contribute to improving the quality and commercial value of the final product. They also stand out in terms of grains per ear and record the highest average dry seed weight and yield. These treatments stand out for the genetic improvement program carried out by the San Gabriel Producers Association (ASGB).